Enhanced Tolerance of Transgenic Potato Plants Over-Expressing Non-specific Lipid Transfer Protein-1 (StnsLTP1) against Multiple Abiotic Stresses - Gangadhar, Baniekal H.; Sajeesh, Kappachery; Venkatesh, Jelli; Baskar, Venkidasamy; Abhinandan, Kumar; Yu, Jae W.; Prasad, Ram; Mishra, Raghvendra K. (Frontiers in Plant Science, 2016)
Abiotic stresses such as heat, drought and salinity are major environmental constraints that limit potato (Solanum tuberosum L.) production worldwide. Previously, we found a potential thermo-tolerance gene, named StnsLTP1 from potato using yeast functional screening. Here, we report the functional characterization of StnsLTP1 and its role in multiple abiotic stresses in potato plants. Computational analysis of StnsLTP1 with other plant LTPs showed eight conserved cysteine residues, and four α-helices stabilized by four disulfide bridges. Expression analysis of StnsLTP1 gene showed differential expression under heat, water-deficit and salt stresses. Transgenic potato lines over-expressing StnsLTP1 gene displayed enhanced cell membrane integrity under stress conditions, as indicated by reduced membrane lipid per-oxidation, and hydrogen peroxide content relative to untransformed (UT) control plants. In addition, transgenic lines over-expressing StLTP1 also exhibited increased antioxidant enzyme activity with enhanced accumulation of ascorbates, and up-regulation of stress-related genes including StAPX, StCAT, StSOD, StHsfA3, StHSP70, and StsHSP20 compared with the UT plants. These results suggests that StnsLTP1 transgenic plants acquired improved tolerance to multiple abiotic stresses through enhanced activation of antioxidative defense mechanisms via cyclic scavenging of reactive oxygen species (ROS) and regulated expression of stress-related genes.